Some aspects of virological study of hydrosphere (Eurasian Journal of Ecology, 2016)
Viruses are an important and integral part of aquatic ecosystems, and the study of the spread of viruses in water bodies with different anthropogenic pressures will allow to diagnose and predict possible changes in the ecological balance in time, and determine the extent of pollution and destruction of studied water bodies.
Keywords: hydrosphere; bioindication; allochthonous viruses; autochthonous viruses virioplanktone